Customer Satisfaction Index Model on Three Level Of Socioeconomic Status In Bogor Case Study: Customer Satisfaction on Branded Cooking Oil Product - Setiawan, Budi (UI Scholars Hub, 2021)
Customer satisfaction index models have been developed in many countries, including Indonesia. Those models were commonly not focused on the socioeconomic status (SES) of the customer, sothis condition could be a research gap. The aims of this research is to analyze the customer satisfaction index model of branded cooking oil product in Bogor, Indonesia based on SES established from the household monthly routine consumption. Questionnaires were used as primary data collection instrument in this study, while data analysis was carried out with variance based structural equation modeling (SEM) which is also known as Partial Least Square (PLS) model, and Kruskall Wallis nonparametric test. Perceived quality, perceived value and customer expectation as were significantly influencing the customer satisfaction construct in the structural model. This study also concluded that there is different level of overall customer satisfaction on the three levels of customer’s SES